2023
DOI: 10.1021/acs.est.3c01040
|View full text |Cite
|
Sign up to set email alerts
|

Tire-Derived Transformation Product 6PPD-Quinone Induces Mortality and Transcriptionally Disrupts Vascular Permeability Pathways in Developing Coho Salmon

Abstract: Urban stormwater runoff frequently contains the car tire transformation product 6PPD-quinone, which is highly toxic to juvenile and adult coho salmon (Onchorychus kisutch). However, it is currently unclear if embryonic stages are impacted. We addressed this by exposing developing coho salmon embryos starting at the eyed stage to three concentrations of 6PPD-quinone twice weekly until hatch. Impacts on survival and growth were assessed. Further, whole-transcriptome sequencing was performed on recently hatched a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 65 publications
(129 reference statements)
1
5
0
Order By: Relevance
“…This has broad implications for the long-term survival and development of lake trout fry. While none of these pathologies have been reported in associated with 6PPD-q exposure, pooling of blood in the caudal fin and eye are consistent with previous studies that have shown changes in vascular and blood-brain barrier permeability in coho salmon following exposure to 6PPD-q 10,19 . It is worth noting that none of the fish exhibiting these pathologies survived the exposure, suggesting that the physiological changes which lead to the development of these pathologies, might be predictive, if not causative, of mortality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This has broad implications for the long-term survival and development of lake trout fry. While none of these pathologies have been reported in associated with 6PPD-q exposure, pooling of blood in the caudal fin and eye are consistent with previous studies that have shown changes in vascular and blood-brain barrier permeability in coho salmon following exposure to 6PPD-q 10,19 . It is worth noting that none of the fish exhibiting these pathologies survived the exposure, suggesting that the physiological changes which lead to the development of these pathologies, might be predictive, if not causative, of mortality.…”
Section: Discussionsupporting
confidence: 91%
“…The wide variation among species is a consistent finding in the study of 6PPD-q as an aquatic contaminant, and so far, phylogeny alone does not seem to be a reliable predictor of sensitivity. Mitochondrial dysfunction has been proposed as a mechanism of action for 6PPD-q toxicity 18 , which has been extrapolated upon 10,19 to include subsequent production of reactive oxygen species and changes in membrane permeability as a mechanism of toxicity. Given the conservation of mitochondrial and electron transport chain physiology among species, it is possible that toxicokinetic factors are a key aspect of the wide-ranging sensitivity of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity mechanism of 6PPD-Q in mammalian cells and aqueous organisms may involve the formation of DNA adducts and the disruption of genomic DNA integrity via reactive oxygen species, leading to oxidative damage such as oxidized base adducts and DNA strand breaks . Additionally, one study highlighted dysregulation of endothelial permeability pathways as a key mechanism in coho salmon, suggesting that disruption of the blood–brain barrier could be a critical pathway for its toxicity . Studies in rainbow trout have demonstrated that significant neurological impairment, alongside disruptions in mitochondrial respiration, is a key contributor to its toxic effects. , …”
Section: Introductionmentioning
confidence: 99%
“…5,6 While the exact mechanism of toxicity remains unknown, it was shown that 6PPD-quinone exposure increases oxygen consumption and mitochondrial dysfunction in gill cells of rainbow trout (RTgill-W1). 7 Other studies investigating the toxic mechanisms of 6PPD-quinone indicated disruption of the blood−brain barrier, 8 as well as induction of DNA adducts in aquatic organisms. 9 While 6PPD-quinone is highly toxic to several species of salmonids, other fishes did not show acute mortality, even when exposed to levels far in excess of environmentally relevant concentrations.…”
Section: ■ Introductionmentioning
confidence: 99%